Consumers' Meat and Products Consumption Frequency, Knowledge Levels and Quality Cues: The Sample of Aksehir, Turkey - Inan, Sumeyra S. Tiske; Bayrak, Ebru; Cebirbay, M. Ali; Aktas, Nazan (Pakistan Journal of Nutrition, 2016)
Meat contains a wide range of important dietary source of proteins and essential nutrients which provide a positive effect on human growth and development. The quality of meat and meat products differ from intrinsic and extrinsic cues so that it can be formed according to preferences of consumers. The aim of this study is to determine the consumer’s consumption frequency, knowledge levels and opinion of quality cues of meat and meat products. The study was conducted as a cross-sectional, general survey model. The sample group of the study consisted of 402 consumers who were selected using easy randomized sampling method. The survey instrument consists of demographic characteristics, consumption frequencies, knowledge level and quality cues of meat and meat products of consumers. According to the results, the participants’ once a week consumption frequencies of beef, mutton/lamb and goat meat were found 23.2, 5.2 and 1.0%, respectively and two-three times a week consumption frequencies of sucuk, pastrami, salami, sausage and braised meat were found 19.7, 1.2, 9.5 and 9.7%, respectively and 3.7% and significantly differences were determined between sucuk, sausage and braised meat (p